2003
DOI: 10.1002/nau.10151
|View full text |Cite
|
Sign up to set email alerts
|

Motor evoked potentials from the pelvic floor

Abstract: The inherent limitations of pelvic floor MEPs are discussed, and it is concluded that while there seems to be only limited clinical value of pelvic floor MEP testing, there might be some interesting scientific perspectives in studies that aim to control and explain the variability of responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 95 publications
0
6
0
2
Order By: Relevance
“…On one hand, a direct EUS response is possible as well as re£ex EUS response via the a¡erent pathways. Most of the data are published for EMG recordings after magnetic stimulation [Brostrom, 2003]. Brodak et al [1993] reported about latencies of the EUS and MEP of the bulbocavernosal muscle in spinal cord injured patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On one hand, a direct EUS response is possible as well as re£ex EUS response via the a¡erent pathways. Most of the data are published for EMG recordings after magnetic stimulation [Brostrom, 2003]. Brodak et al [1993] reported about latencies of the EUS and MEP of the bulbocavernosal muscle in spinal cord injured patients.…”
Section: Discussionmentioning
confidence: 98%
“…Motor latencies to the pelvic £oor could be established which range around 4^10 msec [Opsomer et al, 1989;Vodusek, 1996;Brostrom, 2003] for the electromyographic response depending on the method (surface or needle electrodes, electrical or magnetic stimulation, location of stimulation) and around 27 msec for the urethral pressure response [Schmid et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the sites responsible for the urinary retention in such cases, urological as well as neurological, neurophysiological, and imaging studies are necessary; these studies should include the pelvic nerves (sacral herpes), spinal conus, spinal cord (MRS, ADEM), the pontine micturition centre (PMC) (multiple sclerosis, herpetic brainstem encephalitis), and rarely, the medial frontal lobe. Sacral magnetic stimulation might help to detect any direct involvement of the pelvic nerves [45].…”
Section: Acute Urinary Retention With Csf Abnormality Alonementioning
confidence: 99%
“…Les PEM permettent d'étudier la commande motrice des sphincters ou des muscles du plancher pelvien en enregistrant les réponses EMG à la stimulation magnétique transcrânienne du cortex moteur [26][27][28][29][30][31]. Les temps de conduction sont plus fiables que les valeurs absolues d'amplitude des réponses motrices générées.…”
Section: Potentiels éVoqués Moteurs (Pem)unclassified
“…L'examen est généralement complété par la mesure des LDM en réponse à la stimulation des racines sacrées, ce qui permet de distinguer un temps de conduction « périphérique » (entre les trous sacrés et le muscle où s'effectue le recueil) et un temps de conduction « centrale » (qui comprend les temps de conduction intraencéphalique, médullaire, mais aussi radiculaire intracanalaire). Le recueil peut s'effectuer par électrodes de surface ou à l'aiguille, mais compte tenu de l'activation concomitante des muscles fessiers, un enregistrement à l'aiguille serait plus sélectif et devrait être recommandé [31]. Cette technique permet en théorie de documenter une atteinte centrale supra-sacrée ou de la moelle sacrée qui se manifeste par un allongement du temps de conduction « centrale » aux dépens du temps de conduction « périphérique ».…”
Section: Potentiels éVoqués Moteurs (Pem)unclassified